A novel processing-based classification and conventional food grouping to estimate milk product consumption in Finnish children. (November 2018) - Koivusaari, Katariina; Niinistö, Sari; Takkinen, Hanna-Mari; Åkerlund, Mari; Korhonen, Tuuli; Ahonen, Suvi; Toppari, Jorma; Ilonen, Jorma; Veijola, Riitta; Knip, Mikael; Alatossava, Tapani; Virtanen, Suvi M.
Abstract: As more information is needed about the health aspects of milk processing; we classified milk products based on their homogenisation and heat-treatment history in the following inclusive classes: (i) homogenised, (ii) non-homogenised, (iii) fat-free; and (i) low-pasteurised or less heat-treated, (ii) high-pasteurised at <100 °C, (iii) high-pasteurised at ≥100 °C or sterilised. Milk product consumption of Finnish children was studied at the age of 6 months (n = 1305), 1 y (n = 1513), and 3 y (n = 1328) both using conventional food grouping and the novel processing-based grouping. At 6 months, more than three quarters of the children consumed cows' milk products (median consumption 511 g d −1 ); at 3 y most of the consumed milk products were low-pasteurised or less heat-treated and homogenised. In contrast to children aged 3 y, almost all milk products consumed by infants aged 6 months were pasteurised at high temperature or sterilised.